Aerosols monitoring in Rio Claro, Brazil: Using lidar and air pollution analyzers - Mariano, Glauber Lopes; Lopes, Fabio J.; Steffens, Juliana; Martin, Maria Paulete Pereira; Landulfo, Eduardo; Held, Gerhard [UNESP]; dos Anjos, Sergio [UNESP] (My University, 2011)
Brazil has an important role in the biomass burning aerosol activity. During the Dry Season (June-September) of 2009 an aerosol profiling campaign was carried out using a backscattering and Raman lidar system in Rio Claro-SP, Brazil (22°23'S and 47°32'W). The main goal of this campaign was to observe the biomass burning aerosol load due to sugarcane crops and also study the air dispersion conditions, planetary boundary and mixed layer daily evolution. In this paper we aim to present the preliminary results of the influence of this type of aerosol over the city of Rio Claro-SP, Brazil and one case study to evaluate the aerosol profile in a biomass burning episode that occurred in July, 2009. On July 15 an intense burning was observed about 300 m away from the lidar location. Throughout the measurements it was observed that the plumes reached up to 900 m, and that there was a time gap between the plumes. The gas analyzers showed a strong influence of this burning as it was noticed in the measurements of CO, NO x and nephelometer, whereas the PM10 did not have due to this burning, possibly because the particulate was deposited further from the emission source, not being detected by the equipment. © Sociedad Española de Óptica.
Keywords: Aerosol; Biomass burning; Pollution